Neuronal injury: folate to the rescue? - Golo Kronenberg; Matthias Endres (The Journal of Clinical Investigation, 2010)
Strong epidemiological evidence indicates that derangement of single-carbon metabolism has detrimental effects for proper CNS functioning. Conversely, a role for folate supplementation in the treatment and prevention of neurodegenerative and neuropsychiatric disorders remains to be established. In this issue of the JCI, in an elegant series of experiments in rodents, Iskandar and colleagues demonstrate a crucial role of folate in the regeneration of afferent spinal neurons after injury. Probing sequential steps in folate metabolism, from cellular entry to DNA methylation, the authors show that axonal regeneration relies upon the integrity of DNA methylation pathways. These findings provide the first demonstration of an epigenetic mechanism contributing to neurorepair and suggest that manipulation of the methylation milieu may offer promising new therapeutic avenues to promote regeneration.